2017
DOI: 10.7860/jcdr/2017/26380.10058
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Alcohol Dependency on Oral Health – A Cross-sectional Comparative Study

Abstract: Subjects categorised as alcohol dependent subjects had slightly lower mean plaque and salivary pH and a higher prevalence of dental caries, periodontitis and mucosal lesions compared with non alcoholic subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 23 publications
3
45
0
3
Order By: Relevance
“…One may speculate that it has a negative impact on utilisation of dental care and prosthodontic services. As shown by Priyanka et al, alcohol dependent subjects have higher prevalence of dental caries, periodontitis and mucosal lesions. Moreover, they have reduced interest in seeking and paying for dental care.…”
Section: Discussionmentioning
confidence: 87%
“…One may speculate that it has a negative impact on utilisation of dental care and prosthodontic services. As shown by Priyanka et al, alcohol dependent subjects have higher prevalence of dental caries, periodontitis and mucosal lesions. Moreover, they have reduced interest in seeking and paying for dental care.…”
Section: Discussionmentioning
confidence: 87%
“…There is a high incidence of tooth decay in alcohol addicts, up to three times higher than in people who abstain from drinking alcoholic beverages or drink them rarely [26]. The incidence of dental caries in alcohol addicts is more than double, with trebled incidence of permanent tooth loss [7,26] Furthermore, they also have an increased risk of periodontal diseases which is associated with gingival tissue irritation, poor oral hygiene and dental care, poor dietary habits causing immune depletion and bacterial deposition due to lack of saliva and dehydration [8,27] as well as a serious risk for the development of chronic generalized periodontitis associated with interdental papilla and gingiva inflammation together with formation of periodontal pockets associated with bone loss [27,28].…”
Section: The Direct Effects Of Long-term Alcohol Drinkingmentioning
confidence: 99%
“…Excessive drinking also leads to numerous somatic complications and conditions, including consequences on oral health. Research has shown that heavy drinkers have poorer oral hygiene, dental care, periodontal status, fewer teeth, more carious lesions, gingival diseases, interdental papillae bleeding and deep gingival pockets connected with bone loss as well as a higher rate of oropharyngeal cancers [7][8][9][10]. Non-carious destructions of teeth, including dental erosions, are also linked to frequent drinking due to presence of polyphenols in most alcoholic beverages which leads to precipitation of proline-rich proteins in the saliva [11].…”
Section: Introductionmentioning
confidence: 99%
“…as well as dry mouth [2][3][4][5][6]. The prevalence of dental caries is diminishing in developed countries because of taking preventive measures, while in developing countries the prevalence of dental caries is growing in pediatrics [7].…”
mentioning
confidence: 99%